Prenatal and postpartum zidovudine adherence among pregnant women with HIV: results of a MEMS substudy from the Perinatal Guidelines Evaluation Project. - Ickovics, Jeannette R; Wilson, Tracey E; Royce, Rachel A; Minkoff, Howard L; Fernandez, M Isabel; Fox-Tierney, Rachel; Koenig, Linda J (Journal of acquired immune deficiency syndromes (1999), 2002)
Adherence to HIV treatment regimens during pregnancy may affect efforts to eliminate vertical transmission and influence the emergence of drug-resistant HIV strains that can affect maternal health and the risk of vertically-transmitted resistant strains. Study objectives were to document patterns of adherence to zidovudine (ZDV) during the perinatal period. Pregnant women with HIV who were seen at public clinics, taking ZDV, and willing to use Medication Event Monitoring Systems (MEMS) caps participated in this adherence substudy. Fifty-three women were included in prenatal analyses; however, 19 women were excluded from postnatal analyses because medical records failed to confirm a postpartum maternal prescription for ZDV. Adherence to ZDV, defined as doses per day taken/prescribed during the last 3 weeks of pregnancy, was extremely low (mean = 50.0%), and declined significantly 3 weeks postpartum (mean = 34.1%) (p =.004). Clinical emphasis must be placed on enhancing adherence during and particularly after pregnancy when ZDV is continued for a mother's own care.
Keywords: Adolescent; Adult; Anti-HIV Agents; Female; HIV Infections; Humans; Patient Compliance; Postpartum Period; Pregnancy; Pregnancy Complications, Infectious; Zidovudine